The Effect of Refractivity on Propagation at UHF and VHF Frequencies. (17th November 2016) - Alam, I.; Mufti, N.; Shah, S. A. A.; Yaqoob, M.
Abstract : This paper is using weather parameters to investigate the effect of refractivity on propagation in the first kilometer of the atmosphere over the English Channel for a long transhorizon path of 140 km. Different refractivity profiles are constructed based on meteorological data taken from the UK Meteorological Office in order to investigate the effects of refractivity on propagation. The analysis is made for the hourly experimental path loss between the transmitter and receiver obtained from the experimental setup comprised of two communication links. The frequency of operation of the first link is 2015 MHz and that of the second link is 240 MHz. Parabolic equation method is modelled to get an hourly modelled path loss corresponding to each hourly experimental path loss to be analyzed for the said communication links. The correlation between the modelled path loss and experimental path loss is computed for refractivity distribution recommended by the ITU and predicted profiles. It is inferred from the simulated and experimental results that little or no influence exists by the evaporation duct upon path loss at 2015 MHz specifically for a long path of 140 km over the sea.